Analysis of factors associated with arterial hypertension and the quality of patients’ life - Ch.O. Novak-Mazepa; N.V. Sachuk; M.I. Marushchak (Вісник медичних і біологічних досліджень, 2022)
Summary. Despite the high prevalence of arterial hypertension, awareness and control of blood pressure is quite low in developing countries due to insufficient access to information, inappropriate dietary habits, poverty and high cost of medicines. The aim of the study – to analyze the factors affecting the quality of life of patients with arterial hypertension in order to stratify the main risks and develop a plan of preventive actions on the part of the nurse. Materials and Methods. The study is analyzed scientific publications of the last decade, as well as highly cited publications available on the Internet, keywords were "hypertension", "quality of life of patients", "factors associated with arterial hypertension", "hypertension and quality of life". Results. There is an inverse relationship between hypertension and patients' quality of life. Older patients with hypertension and other comorbidities tend to have a lower quality of life. With age, there is a decline in the quality of life, but only in relation to physical and psychological health. A negative relationship was established between the presence of concomitant pathology and the quality of physical health in patients with hypertension. Gender was also a decisive factor in the quality of life of people with hypertension. Compared to men, women more often ignored the symptoms of hypertension. Regular exercise is one of the important factors affecting the quality of life of people with hypertension. The negative influence of the body mass index on all areas of the quality of life of people with hypertension has been shown. Researchers have found a positive relationship between sleep quality and quality of life. A positive relationship was established between the socio-economic status and the quality of life of patients. Conclusion. Therefore, the lower level of quality of life of patients with arterial hypertension confirms the importance of early diagnosis and correction of the main risk factors of hypertension to preserve the quality of life of these patients. In this context, nurses can directly influence the above-mentioned risk factors by modifying the lifestyle, the level of awareness of the disease, indirectly influencing their quality of life